Cost comparison of steel plate girder and RCC girder bridge. (2022) - Zain, Mohd.; Varma, Rakesh; Srivastava, Rajendra Kumar
Abstract: Most of the part of nation especially city areas facing problem of traffic congestion due to unplanned increasing traffic intensity that is why requirement of elevated road access come into picture. The railway and road crossing is also required the elevated intersection. Most part of the country having superstructure of pre-stressed or RCC structure being heavy in weight creation expensive cost of sub-structure and foundation as well as bearing. A study has been conducted regarding the cost comparison of steel plate Girder Bridge and Reinforced Concrete Girder Bridge and found that steel plate girder is a sustainable option as being light in weight and are more efficient in compression and tension both.